Internationalization from a small domestic base: An empirical analysis of Economics and Management - Ásta Dis Óladóttir (Copenhagen Business School (CBS), 2010)
This dissertation consists of an introductory chapter, followed by four papers that approach the topic of internationalization of small economies and the multinational firm from different angles. The concluding chapter deals with what happened in Iceland after the crisis that started in October 2008 with the collapse of the Icelandic financial system and how the very fast internationalization of Icelandic firms was possible, but only as further issues that need to be researched. Each of the papers can be read individually as well as in the larger context of this dissertation.
hdl:10398/7993
Keywords: 650